Про один підхід до формування рекомендацій щодо удосконалення бізнес-процесів, пов'язаних з постачанням продукції - Орловський, Дмитро Леонідович; Копп, Андрій Михайлович (НТУ "ХПІ", 2014)
Пропонується підхід до формування рекомендацій щодо удосконалення бізнес-процесів, пов’язаних з постачанням продукції, на основі аналізу значень планових та фактичних показників логістичних бізнес-процесів моделі, та подальшого визначення бізнес-процесів, які потребують удосконалення. Для визначення планових показників бізнес-процесів пропонується вирішувати задачу визначення оптимального обсягу замовлення продукції.

Here proposed the approach to the development of recommendations for the improvement of business processes related to the supply of products by analyzing the values of planned and actual performance of the logistics business process model and further define the business processes that need improvement. To determine the targets of business processes is proposed to solve the problem of determining the optimal level of product orders. On the base of math support and algorithms was developed the software for solving the problem of managing supply process of trading enterprise. The software was used to make test calculations. The results of test calculations were used to create recommendations of improving of trading enterprise business process.
About the approach to the development of recommendations for the improvement of business processes related to supply of products
Keywords: конкурентоспроможність підприємства; бізнес-процеси; процесний підхід; управління процесами; торгівельне підприємство; модель SCOR; process management; process approach; business processes; trade enterprise; SCOR model